Comparação entre hemocultura, PCR da hemocultura e PCR do sangue para detecção do Trypanosoma cruzi em pacientes na fase crônica da infecção - Piovesani, Ana Flávia de Arruda (2015)
For Chagas disease diagnosis, the hemoculture is a parasitological method with high specificity but with low sensitivity and the PCR is a more sensitive molecular method. In order to combine the specificity of the hemoculture and sensitivity of the PCR, we have proposed to perform the PCR from samples obtained from the hemoculture (PCR-HC) of 79 patients in the chronic phase of infection. In addition to the PCR-HC, the methods of hemoculture and PCR of blood (PCR-BL) were performed. To carry out the hemoculture, 30 mL of blood were used and to the PCR-HC and PCR-SG, 2.4 mL of sediment of the hemoculture and 10 mL of blood was added to an equal volume of Guanidine-EDTA, respectively. The DNA was extracted of each sample and the fragment of 330 base pair from Trypanosoma cruzi minicircle was amplified. The PCR-HC (p=0.00005) and the PCR-BL (p=0.00121) were significantly more positive than the hemoculture. The positivity of the PCR-HC was also significantly higher (p=0.00032) than the PCR-BL. We have concluded that the positivity of the PCR-HC is greater than PCR-BL and hemoculture, which may constitute a valid alternative method to increase the detection of the parasite, improving the parasitological diagnosis and identification of treatment failure.